Continuity and transformation of Islamic educational institutions in Palembang’s Malay Civilization (1900–Present) - Nurfitria Dewi (Kuras Institute, 2026)
Purpose − This study examines the continuity of Islamic educational institutions within the context of Palembang Malay civilization from 1900 to the present. This study aims to analyze the ongoing role of Islamic educational institutions in shaping and preserving Malay Islamic civilization in Palembang through a multitemporal review, from the Dutch colonial era to the contemporary era. Method − Using historical research methods with a qualitative approach, data were collected through heuristics, source criticism (external and internal), and in-depth interviews with key figures and alumni. Findings − The research findings indicate a significant shift in the role of Palembang's Islamic educational institutions, from a focus on ideological and cultural resistance during the colonial period to a focus on developing superior human resources today. During the colonial era, Islamic educational institutions served as a bulwark against Westernization, with the curriculum dominated by religious knowledge to instill anti-colonial values. Post-Independence, this role transformed into formal consolidation and institutionalization through state recognition and the establishment of Islamic universities (such as UIN Raden Fatah). Today, Islamic educational institutions firmly integrate religious and general knowledge, with an orientation toward producing professionals with noble character who can compete in the era of globalization. Despite this shift in focus, elements of continuity are found in the commitment of Islamic educational institutions to the fundamental values of wasathiyah (moderate) Islam and the preservation of Malay customs. This ongoing role confirms that Islamic educational institutions are adaptive agents of historical change and guardians of civilizational identity in Palembang.